IDENTIFIKASI KEGAGALAN PADA KOMPONEN PITOT PROBE BOEING 737-900ER - Cristhina, Cristhina; Mulyani, Sri; Priyahapsara, Istyawan (Institut Teknologi Dirgantara Adisutjipto, 2023)
Based on Boeing 737-900ER unscheduled removal data of pitot probe 0851HT-1 January, 2020 to November, 2021 found 14 removal for pitot probe with one of the defect is “pitot light on”. This indicate that there is a problem with the component and can disrupt the pilot and delay the aircraft. Knowing the result of failure identification and the type of failure be the aim of this research. Analysis using Failure Mode and Effect Analysis used to identify failure modes, causes and effects of failure, severity, occurrence, and detection ranking so that the risk priority number obtained. Based on the FMEA Worksheet, there are 8 failure modes that occur on the pitot probe with the highest Risk Priority Number is 126 on mode “IAS AND ALT DISAGREE”.